Hedysari extract improves regeneration after peripheral nerve injury by enhancing the amplification effect. - Zhiyong Wang (Public Library of Science (PLoS), 2013)
Radix Hedysari is an herbal preparation frequently used in traditional Chinese medicine. It can promote regeneration after peripheral nerve injury, but its effect on the amplification ratio (the ratio of distal to proximal fibers) during peripheral nerve regeneration has not yet been examined. In this study, we explored the effect of Hedysari extract on the amplification ratio in the peripheral nerve. Male Sprague-Dawley rats were separated into three groups at random: normal group (without surgery), model group (given sleeve nerve bridging surgery, but without adjuvant treatment) and treatment group (given sleeve nerve bridging surgery and then given Hedysari extract as adjuvant treatment). Twelve weeks after surgery, general observations, electrophysiological examination, histological analysis, morphometric measurements, and amplification ratio calculations were made. The results showed that nerve conduction velocity, the fiber and axon diameter, the g-ratio, the number of regenerating nerve fibers and the amplification ratio were better in the treatment group than in the model group, suggesting that Hedysari extract can effectively promote the growth of lateral buds in the proximal nerve stump and substantially improve the amplification effect during peripheral nerve regeneration.